Pengaruh Program Pemutihan Pajak, Sistem Samsat Drive Thru dan Penerapan E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Motor di Kantor Samsat Tabanan - Putra, I Putu Agus Candra; Sudiana, I Wayan; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2025)
Motor veìhiìcleì tax iìs a reìgiìonal tax wiìth a veìry poteìntiìal sourceì of local iìncomeì, thiìs can beì seìeìn from theì iìncreìaseì iìn theì numbeìr of veìhiìcleìs whiìch from yeìar to yeìar theì iìncreìaseì iìs veìry siìgniìfiìcant. Iìf eìveìry communiìty or taxpayeìr iìs compliìant iìn makiìng paymeìnt of motor veìhiìcleì tax, theìn theì poteìntiìal iìncomeì of theì reìgiìon that comeìs from motor veìhiìcleì taxeìs wiìll beì comparableì to theì iìncreìasiìng numbeìr of motor veìhiìcleìs eìach yeìar. But theì facts on theì ground areì reìveìrseìd, theì iìncreìaseì iìn theì numbeìr of motor veìhiìcleìs doeìs not guaranteìeì an iìncreìaseì iìn motor veìhiìcleì tax reìceìiìpts. Theì aiìm of thiìs study iìs to fiìnd out theì iìmpact of theì Tax Reìfiìneìmeìnt Program, theì Samsat Driìveì Thru Systeìm, and theì iìmpleìmeìntatiìon of Eì-Samsat on theì compulsory compliìanceì of motor veìhiìcleì tax at Samsat Offiìceì Tabanan. Theì populatiìon of thiìs study iìs as many as 100 reìspondeìnts obtaiìneìd wiìth theì Sloveìneì formula. Sampliìng teìchniìqueì usiìng random sampliìng teìchniìqueìs. Data from thiìs study was colleìcteìd by spreìadiìng theì queìstiìonnaiìreì whiìch was theìn analyzeìd wiìth a doubleì liìneìar reìgreìssiìon teìst. Theì reìsults of thiìs study showeìd that theì tax cleìaranceì program and theì iìmpleìmeìntatiìon of eì-samsat had no siìgniìfiìcant iìmpact on tax compliìanceì, whiìleì theì systeìm of samsat driìveì thru had a posiìtiìveì and siìgniìfiìcant eìffeìct on compliìanceì wiìth tax obliìgatiìons